Photothermal Möbius aromatic metallapentalenofuran and its NIR-responsive copolymer. Issue 16 (22nd March 2018) - Lu, Zhengyu; Cai, Yuanting; Wei, Yuanqing; Lin, Qin; Chen, Jiangxi; He, Xumin; Li, Shunhua; Wu, Weitai; Xia, Haiping
Abstract : A novel thermally and NIR-light responsive metallopolymer was copolymerized from a photothermal aromatic metallapentalenofuran and a glycol methyl ether methacrylate. Abstract : Möbius aromatics are very interesting and rare complexes owing to their brand-new chemistry and interesting properties. In this work, metallapentalenofurans with thiophene groups were easily prepared from the reaction of metallapentalyne, terminal arylalkynes, and water in air. The metallapentalenofuran containing a terthiophene moiety showed a good photothermal effect and was the first photothermal Möbius aromatic complex induced by J -aggregates. This photothermal metallapentalenofuran was chemically modified to carry an olefinic group and then was co-polymerized with oligo-(ethylene glycol)methacrylate to afford a thermoresponsive copolymer, whose phase transition behavior can be triggered by near-infrared radiation at 808 nm. This near-infrared-responsive metal-containing copolymer represents a new stimuli-responsive macromolecule.